Analysis of the Supreme Court Decision that Canceled the Decision of the Jakarta Commercial Court in the PKPU Case of PT Asuransi Jiwa Kresna - Asri, Meidi; Noerhadi, Cita Citrawinda; Mardani, Mardani (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2023)
This study aims to analyze 1) the Judge’s legal considerations in granting the application for Postponement of Debt Payment Obligations (PKPU) against PT Asuransi Jiwa Kresna filed by Policyholders, 2) the suitability of Decision Number 647 K/Pdt.Sus-Bankruptcy/2021 dated June 8, 2021, with Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. Normative juridical research with a statutory approach and case approach. Primary and secondary legal data are analyzed by concluding a general problem to the concrete problem at hand. The results showed that 1) The Panel of Judges granting PKPU applications in civil procedural law must be proven by the parties to civil litigation, not the law, but the event or legal relationship. In civil cases, the judge must conduct an assessment of the events submitted by the litigants, and then separate which events are important and which are not important. It is the important events that must be proven. The means of evidence include written letters, evidence by witnesses, and presumptive evidence. 2) The conformity of Decision Number 647 K/Pdt.Sus-Bankruptcy/2021 with Law Number 37 of 2004 concerning Bankruptcy and PKPU in this case, which is a bankruptcy case, follows the procedure for civil proceedings in general. However, evidence was provided simultaneously with the submission of the application to the clerk. The evidence was that the transactions carried out by the respondent were not following the homologation agreement, regardless of whether the debt owed by the respondent to the applicant was paid off.